Experimentally evaluating electrical outputs of a PV-T system in Jordan - Issa Etier; Salem Nijmeh; Mohammed Shdiefat; Omar Al-Obaidy (Institute of Advanced Engineering and Science, 2021)
This experimental work is looking at the properties of photovoltaic/thermal (PV-T) system, which had designed to increase the output power of the PV panel for the climate of Zarqa, Jordan. Operating temperature of the PV module has a significant impact on the performance of the PV module. However, most of the radiation energy absorbed by the PV panel is converted into heat, which is normally lost and provides no value. In order to decrease the operating temperature of the PV panel, a water cooling system with a control system had designed. Experimentally, when the PV module was operating under active water-cooling condition using the backside cooling technique, the temperature dropped significantly, which led to an increase in the electrical efficiency of solar cells by 6.86%.